2018
DOI: 10.1186/s11671-018-2435-3
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Nickel Oxide (NiO) Nanopetals for Ultrasensitive Glucose Sensing

Abstract: Glucose sensing properties of mesoporous well-aligned, dense nickel oxide (NiO) nanostructures (NSs) in nanopetals (NPs) shape grown hydrothermally on the FTO-coated glass substrate has been demonstrated. The structural study based investigations of NiO-NPs has been carried out by X-ray diffraction (XRD), electron and atomic force microscopies, energy dispersive X-ray (EDX), and X-ray photospectroscopy (XPS). Brunauer–Emmett–Teller (BET) measurements, employed for surface analysis, suggest NiO’s suitability fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 38 publications
3
47
1
Order By: Relevance
“…The sensitivity recorded in the current study using the wireless device (Au/Pt-black/Nf MNEA) is greater than the several non-enzymatic glucose sensors reported earlier [ 29 , 30 , 32 , 33 , 34 , 35 ]. The linear range reported in the present study is greater than many of the enzyme-free glucose sensors reported in the past decade [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultscontrasting
confidence: 55%
“…The sensitivity recorded in the current study using the wireless device (Au/Pt-black/Nf MNEA) is greater than the several non-enzymatic glucose sensors reported earlier [ 29 , 30 , 32 , 33 , 34 , 35 ]. The linear range reported in the present study is greater than many of the enzyme-free glucose sensors reported in the past decade [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultscontrasting
confidence: 55%
“…Therefore, a worldwide parallel study is conducted in either finding the new nano materials or designing new morphologies for achieving better performance of different applications [5,13,14]. A huge number applications of TMO like supercapacitor [15], field emission [16], sensors [17], photocatalytic [18], hydrogen/oxygen evolution [19], electrochromic [4] and so forth demonstrates excellent performance by incorporating the different dimension-based nanostructures like nanodot [20], nanosheet, nanorod [21], nanoneedle, nanoflakes [21] and so forth. Among these, electrochromic (EC) application [22][23][24][25][26][27] also depends upon morphologies for obtaining the higher surface area of the particular architecture to make contact with the electrolyte immensely.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, CPs are in increasing demand because they are biocompatible, solution-processable, and inexpensive in nature. CP NSs exhibit high electrical conductivity, large surface area, short path lengths for the ion transport, and superior electrochemical activity compared to their bulk counterparts, which make them suitable for various applications. Further, hybrid combinations of CPs with inorganic NSs show their combined properties and is found to be suitable for various applications. , At the same time, tuning the nanoscale morphology proves to be very efficient in electrochemical-based application such as supercapacitors, , electrochromic displays, , water splitting, sensors, etc. Along with the general properties of these hybrid NSs, their tunable structures prove them to be outstanding functional segments or building blocks for various nanomaterial-based devices. , The nanowire- or nanofiber-type shell of electrochromically active CP on transition-metal oxides (TMOs) shows a change in color as a result of electric bias.…”
Section: Introductionmentioning
confidence: 99%